A THERAPIST-DENTIST PERSPECTIVE ON THE ROLE OF CYTOKINE CHANGES IN THE PATHOGENESIS OF PERIODONTAL DISEASE IN YOUNG PERSONS - N.V. Hasiuk; I.P. Misterman; V.B. Radchuk; S.S. Bozhik (Український стоматологічний альманах, 2024)
The issue of expanding the understanding of the aetiology and pathogenesis of periodontal diseases is a pertinent one, and one that is frequently requested by the dental community, comprising professionals with a range of specialisations. A significant number of works from this direction show that in the etiology and pathogenesis of pathological processes of the periodontium, a significant role belongs to the microbial factor, in particular to representatives of the saprophytic and conditionally pathogenic microflora. In response to bacterial peptidoglycans, epithelial cells of the oral cavity synthesize a number of cytokines, which are a component of natural immunity.